Virtual learning for safety, why not a smartphone? - Desai, Nishaben Padam; Ferjenčík, Miloš; Schofield, Damian; Kubik, Jan (Wiley; American Institute of Chemical Engineers, 2019)
This article aims to examine the effectiveness of a Virtual Learning Environment (VLE) using Kolb's Experiential Learning Theory (ELT) for chemical laboratory safety. A VLE model of a distillation column rig situated at the chemical engineering department, at the University of Nottingham (UK) was designed for the purpose of safety and hazard awareness training for first year laboratory students. The basic pedagogical ideas behind the model were to compare the effectiveness of passive learning used in traditional safety training with the way a VLE can deliver an active learning platform. Based on the collected experience, this article investigates issues that arose while correlating a VLE model with Kolb's ELT. Some of the drawbacks of the VLE model have been taken into consideration while designing a mobile game application for the purpose of laboratory safety training at the Research Laboratory of Energetic Materials at Pardubice University (Czech Republic). This is believed to offer more scope to develop constructivist learning using a smartphone. (c) 2018 American Institute of Chemical Engineers Process Saf Prog 38: e12005, 2019
Virtuální výuka bezpečnosti, proč ne se smartphonem?
Keywords: safety training; Kolb's learning cycle; constructivism; mobile serious games; bezpečnostní vzdělávání; bezpečnostní výcvik; vzdělávací mobilní hry